Projection of Effectiveness, Efficiency, and Regional Independence of Gorontalo Province - Rasid, Ayub Usman; Masia, Israwanto; Hasyim, Hasyim (Gorontalo Development Review, 2025)
This article examines the projection of Gorontalo Province's financial performance in the context of the decentralization of the Indonesian government that has been going on since 1999. Although decentralization provides greater autonomy in the management of resources and public services, Gorontalo Province still faces significant challenges in optimizing Regional Original Revenue (PAD) and a high dependence on fund transfers from the central government. Using a quantitative approach and descriptive methods, this study analyzes secondary data from the Gorontalo Governor's Accountability Report (LKPJ) for the 2019-2023 period. The analysis was carried out using three financial ratios – effectiveness, efficiency, and regional independence – which were then projected for the 2024-2033 period using linear trend analysis. The projection results show interesting dynamics: a decrease in the effectiveness ratio from 99.50% to 39.71%, an increase in efficiency from the status of "Less Efficient" (94.71%) to "Efficient" (78.11%), and the strengthening of regional independence from the category of "Low" (41.68%) to "Medium" (66.60%). These findings indicate serious challenges in achieving revenue targets, but also show the potential for improvement in expenditure management and regional independence. This research makes an important contribution to the long-term understanding of regional financial performance and suggests the need for further research that takes into account external factors such as national policy changes, global economic dynamics, and potential economic shocks.